2018
DOI: 10.1097/ta.0000000000001940
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure during emergency department thoracotomy: A prospective, multi-institution study

Abstract: Therapeutic/care management study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…In a trauma centre study, the compliance rates for use of masks and eye protection, after an educational intervention, were 16% and 44%, respectively [26]. ED clinicians are regularly at risk of facial contamination during invasive procedures, intubation and other resuscitative measures [27]. They are also exposed to both seasonal and emerging respiratory infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In a trauma centre study, the compliance rates for use of masks and eye protection, after an educational intervention, were 16% and 44%, respectively [26]. ED clinicians are regularly at risk of facial contamination during invasive procedures, intubation and other resuscitative measures [27]. They are also exposed to both seasonal and emerging respiratory infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, resuscitation of these patients requires a substantial reallocation of resources, which invariably distracts from the care of other ED patients. In addition, resuscitative thoracotomies convey a measurable risk to physician staff performing the procedure 12 . Previous work has been done on attempts to identify patients with higher chances of survival including point‐of‐care ultrasound; however, a persistent limitation in the care of these patients is the lack of reliable total downtime 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the ACS Committee on Trauma and the American College of Emergency Physicians (ACEP) issued a joint statement outlining indications for REBOA [41]. They also provided guidelines for REBOA use and implementation, patient transfer and management EDT is associated with an increased risk of provider occupational injury and exposure to trauma patient blood-borne illnesses [26,30]. Studies conducted in the United States have reported that the prevalence of human immunodeficiency virus (HIV) and hepatitis C virus infection among trauma patients may approach 4.3% and 14%, respectively [30].…”
Section: Edtmentioning
confidence: 99%
“…They also provided guidelines for REBOA use and implementation, patient transfer and management EDT is associated with an increased risk of provider occupational injury and exposure to trauma patient blood-borne illnesses [26,30]. Studies conducted in the United States have reported that the prevalence of human immunodeficiency virus (HIV) and hepatitis C virus infection among trauma patients may approach 4.3% and 14%, respectively [30]. In a multicenter prospective cohort study conducted across 16 predominantly level 1 American trauma centers, 7.2% of 305 EDTs were complicated by occupational exposures [30].…”
Section: Edtmentioning
confidence: 99%
See 1 more Smart Citation